2003
DOI: 10.1007/s00431-003-1356-y
|View full text |Cite
|
Sign up to set email alerts
|

Advances in analytical mass spectrometry to improve screening for inherited metabolic diseases

Abstract: This overview aims to describe only current new developments in clinically most relevant applications, in particular with focus on low molecular weight compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 68 publications
(46 reference statements)
0
30
0
4
Order By: Relevance
“…Mass spectrometric assays revolutionized the diagnosis of inherited metabolic disorders, a development co-pioneered in the late 1990s by Adelbert Roscher (Röschinger et al, 2003). This and similar pilot projects around the world taught the diagnostics community some crucial lessons.…”
Section: Technological Advances Paved the Way Into Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometric assays revolutionized the diagnosis of inherited metabolic disorders, a development co-pioneered in the late 1990s by Adelbert Roscher (Röschinger et al, 2003). This and similar pilot projects around the world taught the diagnostics community some crucial lessons.…”
Section: Technological Advances Paved the Way Into Clinical Applicationsmentioning
confidence: 99%
“…Furthermore, it has been proven for many disorders that multiparametric biomarkers reduce biological noise in the data by internal normalization as well as improve diagnostic sensitivity and specificity. Subsequently, it led to a marked reduction of healthcare costs (Röschinger et al, 2003;Weinberger., 2008).…”
Section: Technological Advances Paved the Way Into Clinical Applicationsmentioning
confidence: 99%
“…Many metabolic conditions appear to be identifiable with relatively little cost 69,70 and a small sample of blood. However, there is insufficient literature on the clinical application at this time to judge its appropriateness in the evaluation of the child with DD/MR.…”
Section: Metabolic Studiesmentioning
confidence: 99%
“…Because the technology is used for newborn screening programs, the clinical utility in other settings, such as the evaluation of children who might be clinically symptomatic, is being discussed. 69,71 Studies addressing the optimal metabolic evaluation of patients with DD/MR are needed.…”
Section: Metabolic Studiesmentioning
confidence: 99%
“…Targeted MS analyses with higher sensitivity are currently utilized to address these shortcomings (1,2); however, these studies often only analyze a small list of proteins identified as biologically significant. While targeted MS measurements are increasingly common in clinical applications (3,4), the limited number of proteins they examine does not necessarily reflect the biodiversity across a population, making broad untargeted measurements essential in developing individual disease metrics for diagnosis (5). As the future of medicine proceeds toward a personal profiling approach (6,7), the potential for robust high throughput clinical measurements based upon MS is highly attractive, though only if its deficiencies can be addressed.…”
mentioning
confidence: 99%